2021
DOI: 10.1111/ejn.15257
|View full text |Cite
|
Sign up to set email alerts
|

Is there a single beta oscillation band interfering with movement in Parkinson's disease?

Abstract: Beta oscillations in basal ganglia are considered to contribute to motor dysfunction in Parkinson's disease (PD). However, there is a high variety in frequency borders for beta oscillations between studies, which complicates the comparison and interpretation of results. Here we aimed to study the homogeneity of oscillations in the broad "beta" range (8-30 Hz) and their implication to motor functioning in PD. For this purpose, we recorded local field potentials (LFP) in the subthalamic nucleus (STN) during 34 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…When inspecting prominent peaks in the bands identified by the clustering approach, we identified two groups of patients (with and without prominent oscillations covering the α‐β range) who differed in several features. Patients with prominent lower‐frequency oscillations had significantly higher bradykinesia and rigidity scores that correspond well with previous findings 4,19 . Noteworthy, we observed prominent single‐peak β activity in all patients in both groups, whereas only about a half of patients had additional high‐amplitude α‐β oscillation peaks in their LFP recordings.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When inspecting prominent peaks in the bands identified by the clustering approach, we identified two groups of patients (with and without prominent oscillations covering the α‐β range) who differed in several features. Patients with prominent lower‐frequency oscillations had significantly higher bradykinesia and rigidity scores that correspond well with previous findings 4,19 . Noteworthy, we observed prominent single‐peak β activity in all patients in both groups, whereas only about a half of patients had additional high‐amplitude α‐β oscillation peaks in their LFP recordings.…”
Section: Discussionsupporting
confidence: 90%
“…Although the exact frequency borders for particular oscillatory ranges in PD research vary considerably across the studies, only very few research studies have directly inspected probable heterogeneity of the broad β range regarding the strength of its association with motor symptoms 4,19 . Remarkably, when examining consequent frequency bins along the power spectra, both aforementioned studies have found the strongest associations with hypokinetic symptoms in the α‐β range (8–16 and 10–15 Hz, respectively), not the conventional β frequency (with the lower‐frequency border commonly set as 13 Hz).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations